Quantum dot bioconjugates: emerging tools with great potential to study protein interactions and dynamics by FRET. (8th February 2011) - Galvez, Eva M.; Pardo, Julian
Methods based on fluorescence technology have been widely employed to analyse protein function, dynamics, interactions and folding in cell free systems as well as in intact cells. Fluorescence resonance energy transfer (FRET) is a unique technique to precisely calculate inter- and intra-molecular distances in proteins and thus to study protein-protein/peptide interaction, folding and conformational changes. However detailed studies of these processes at the single molecule level and/or in intact cells, requires fluorescence dyes with high stability and quantum yield. During the last six years fluorescent nanocrystals (quantum dots) have been developed as potent and promising fluorescence dyes that fulfil the prerequisites to study protein function in FRET based assays. It is the aim of this short review to summarise the benefits and drawbacks of QDs in the study of protein function and dynamics in biological systems.